Pathogenicity and behaviour of Ditylenchus destructor (Nematoda: Tylenchidae) on groundnut (Arachis hypogaea) - Venter, Cheryl (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.